1998
DOI: 10.1164/ajrccm.158.1.9706048
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Salmeterol versus Doubling the Dose of Beclomethasone in Children with Asthma

Abstract: Studies in adults revealed that addition of salmeterol to a moderate dose of inhaled corticosteroid resulted in better symptom control and higher PEF compared with doubling the dose of inhaled corticosteroid. The aim of this three group study was to compare the effects of a moderate dose of beclomethasone, the same dose of beclomethasone with salmeterol, and a doubling dose of beclomethasone on lung function and symptoms in children with moderate asthma. A total of 177 children already treated with inhaled cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
3
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(149 citation statements)
references
References 29 publications
6
130
3
5
Order By: Relevance
“…For all children, but particularly for those aged f5 yrs, combination therapy has been less well studied, and the addition of a long-acting b 2 -agonist may not be as effective as increasing the dose of inhaled glucocorticosteroids in reducing exacerbations [182,291,292]. However, the interpretation of some studies is problematic, as not all children received concurrent inhaled glucocorticosteroids [182,291].…”
Section: Treatment Steps For Achieving Controlmentioning
confidence: 99%
“…For all children, but particularly for those aged f5 yrs, combination therapy has been less well studied, and the addition of a long-acting b 2 -agonist may not be as effective as increasing the dose of inhaled glucocorticosteroids in reducing exacerbations [182,291,292]. However, the interpretation of some studies is problematic, as not all children received concurrent inhaled glucocorticosteroids [182,291].…”
Section: Treatment Steps For Achieving Controlmentioning
confidence: 99%
“…Verberne et al showed in a prospective randomised controlled study that children with moderate severe asthma did not benefit from doubling their dose of ICS, or from addition of a LABA to their ICS. 17 Some authors have even suggested a worsening of asthma control by treatment with the combination of an ICS and a LABA. Bisgaard found that the relative risk of an asthma exacerbation as well as the risk of hospitalisation for asthma was increased for children using additional LABA compared to regular maintenance therapy with ICS; 18 he concluded that the lack of evidence for the control of asthma exacerbations in children regularly using a LABA should bring into question its general use as add-on therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the preferred option is to increase ICS to medium dose (see Box 3-6, p.44), 172 and in this age group, the effect may be similar to 173 or more effective 174,175 than adding LABA.…”
Section: Preferred Option (Adults/adolescents): Combination Low Dose mentioning
confidence: 99%